Breeding and juvenile growth of the ribbontail stingray Taeniura lymma at Oceanário de Lisboa - Ferreira, Ana Santos,1982- (2014)
Tese de mestrado. Biologia (Biologia da Conservação). Universidade de Lisboa, Faculdade de Ciências, 2013